1997
DOI: 10.1103/physrevb.55.2188
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of interstitial carbon and carbon-carbon pair defects in silicon

Abstract: Interstitial carbon, C i , defects in Si exhibit a number of unexplained features. The C i defect in the neutral charge state gives rise to two almost degenerate vibrational modes at 920 and 931 cm Ϫ1 whose 2:1 absorption intensity ratio naturally suggests a trigonal defect in conflict with uniaxial stress measurements. The dicarbon, C s -C i , defect is bistable, and the energy difference between its A and B forms is surprisingly small even though the bonding is very different. In the B form appropriate to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
43
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 23 publications
16
43
2
Order By: Relevance
“…The results obtained by the PBEsol functional only agree with the experimental value in the energetic order for the charge neutral state, while the value is substantially larger. Our HSE calculations yield results that agree with the experiment better than previous theoretical studies, [32][33][34] except for the À1 charge state for which the total energy difference is 0.07 eV, while the experimental value is À0.04 eV. The total energy difference for the charge neutral state is found to be 0.04 eV, which is very close to the experimental value of 0.02 eV, and for the þ1 charge state the value of À0.09 eV is also qualitatively comparable to the experimental result of À0.02 eV.…”
supporting
confidence: 69%
“…The results obtained by the PBEsol functional only agree with the experimental value in the energetic order for the charge neutral state, while the value is substantially larger. Our HSE calculations yield results that agree with the experiment better than previous theoretical studies, [32][33][34] except for the À1 charge state for which the total energy difference is 0.07 eV, while the experimental value is À0.04 eV. The total energy difference for the charge neutral state is found to be 0.04 eV, which is very close to the experimental value of 0.02 eV, and for the þ1 charge state the value of À0.09 eV is also qualitatively comparable to the experimental result of À0.02 eV.…”
supporting
confidence: 69%
“…[30][31][32] Using the AIMPRO method, Leary et al estimated the activation energy to be 1.10 eV. 33 Since a smaller cluster ͑87 atoms͒ and a smaller basis was used than in the present work, it is reasonable to expect that the results given here for C i in GaAs are more reliable than previously obtained for C i in Si. A less sophisticated procedure was also employed to determine the migration path, which tends to overestimate the barrier.…”
Section: Methodscontrasting
confidence: 54%
“…[17][18][19] These defects in turn introduce states within the Si band gap, which can impact devices [20][21][22] and therefore their structure and properties have been thoroughly investigated. [23][24][25][26][27] Finally, during irradiation Ci, CiOi, and CiCs defects are nucleation centres for more extended defects such as CiOiSiI. [28][29][30] The experimental studies of Watkins 31,32 and Kimerling et al 33 demonstrated that isovalent impurities [carbon (C), germanium (Ge) and tin (Sn)] can impact the formation processes of VO pairs in Si.…”
Section: Introductionmentioning
confidence: 99%